Nano-confined magnesium for hydrogen storage from reactive milling with anthracite carbon as milling aid - Zhou, Shixue; Zhang, Xiaoli; Li, Tao; Wang, Naifei; Chen, Haipeng; Zhang, Tonghuan; Yu, Hao; Niu, Haili; Liu, Di (International journal of hydrogen energy, 2014)
The structure and properties of magnesium nanoparticles for hydrogen storage from reactive milling under hydrogen atmosphere with the carbon from anthracite coal carbonization as milling aid were investigated. Experiment showed that after 3 h of milling under 1 MPa of hydrogen with 30 wt.% of carbon additive, the magnesium particles were milled to 20–60 nm and hydrided into β-MgH2 with a crystallite size of 29.7 nm. For the hydrogen desorption of the material, the onset temperature was determined to be 270 °C. In 270–390 °C, the enthalpy and entropy changes were calculated to be 44.5 kJ/mol and 83.8 J/(mol K), respectively, and the activation energy as pseudo first-order reaction was 127.1 kJ/mol. The carbon still played a role of nano-confinement for magnesium to prevent particles from coalescing in the process of repeatedly heating for hydrogen storage. •Carbon from anthracite coal is an effective milling aid to prepare Mg nanoparticles.•Carbon plays a role of nano-confinement to Mg during heating for H2 sorption.•With extension of milling time, more β phase of MgH2 can convert into γ phase.•Crystal defects and γ phase of MgH2 results in decrease of thermodynamic stability.•Particle size and crystal defects of MgH2 influence H2 sorption kinetics.